2010
DOI: 10.1021/ma100184h
|View full text |Cite
|
Sign up to set email alerts
|

Polyampholyte Microgels with Anionic Core and Cationic Shell

Abstract: We report synthesis of amphoteric microgels by copolymerization of N-vinylcaprolactam (VCL), itaconic acid dimethyl ester (IADME), and vinylimidazole (VIm) in the precipitation−polymerization process. After hydrolysis of ester groups of IADME, component microgels contain acidic and basic groups in their structure. Proton high-resolution transverse magnetization relaxation under magic angle sample spinning (MAS) was used to measure the dynamic heterogeneity corroborated with the chemical structure of a multicom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 48 publications
2
113
0
1
Order By: Relevance
“…However, the flocculated microgels could be easily redispersed by either an increase or a decrease in pH of the medium. We have found that the hydrodynamic diameters of microgels 3c-e, 4b, 5,6, and 7b at pH2 and pH8.5 are almost the same, which is an evidence of the swollen state of the microgels (Table 1). This result is quite similar to the behaviors observed in the cases of other polyampholyte polymers and their gels [4,8].…”
Section: Microgel Propertiesmentioning
confidence: 72%
See 1 more Smart Citation
“…However, the flocculated microgels could be easily redispersed by either an increase or a decrease in pH of the medium. We have found that the hydrodynamic diameters of microgels 3c-e, 4b, 5,6, and 7b at pH2 and pH8.5 are almost the same, which is an evidence of the swollen state of the microgels (Table 1). This result is quite similar to the behaviors observed in the cases of other polyampholyte polymers and their gels [4,8].…”
Section: Microgel Propertiesmentioning
confidence: 72%
“…In the last years, most attention was paid to polyampholyte microgels, which belong to smart materials due to their response to temperature, pH, ionic strength, water-organic solvent composition, electric field, etc. Various microgels bearing amino and carboxyl groups have been obtained on the basis of synthetic and natural polymers [4][5][6] including polysaccharides [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This data indicates that the aggregation of p(4-VP) microgels in aqueous solutions is pH dependant. Furthermore, the location of charged moieties at the surface and/or inside the microgel affects the aggregation of microgels at different pH values [46][47][48]. It is expected that when they are located at the surface of the microgel, the pH-dependent ionization will lead to a good interaction of the particles especially at the surface.…”
Section: Aggregation Of the P(4-vp) Microgels In Watermentioning
confidence: 99%
“…Our previous results on an amphoteric microgel, obtained by copolymerization of VCL, itaconic acid dimethylester (IADME) and vinylimidazole (VIm), using 1 H highresolution site-selective transverse relaxation NMR also showed a bimodal transverse relaxation behavior indicating a heterogeneous core-corona internal structure. [ 19 ] Efforts were made in order to describe the swelling behavior of microgels using improvements on the Flory's thermodynamic theory for gel systems. [ 20 , 21 ] A combination of the extended Flory-Huggins model [ 22 , 23 ] for mixing solvent and network with a modifi ed Flory-Rehner theory [ 24 ] for elastic contribution was used and fi tted to experimental data obtained for submicron gel particles and bulk gels.…”
Section: Dynamic Light Scattering (Dls)mentioning
confidence: 99%